PROFIL KECERDASAN EMOSIONAL PADA SISWA BIOLOGI DI SMA NEGERI 2 TAMBANG - Tiovani, Dewi; Arnentis, Arnentis; Suryawati, Evi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: Emotional intelligence has a greater contribution in determining the success of biology lesson in school. Most student rely on intellectual abilities to support their learning success. This study aims to determine the emotional intelligence profile of biology students. This research was conductedat SMA Negeri 2 Tambang in August 2020. This type of research is a descriptive study. The sampling technique used was saturated sampling technique so that the sample in this study were 173 students. The instruments used in data collection were a closed questionnaire and an open questionnaire. The questionnaire trial data was tested for validity and reliability using a computer program, namely Microsoft Excel. The results showed that the average indicator of students emotional intelligence was good. There are four indicators of emotional intelligence that are included in the good category, including students self-awareness with a mean of 3.18, self-regulation has a mean of 2.94, student motivation with an average of 3.31, ang student empathy has a mean of 3.20. the fifth indicator, namely social skills, has a mean of 3.25 with very good category.Key Words: Emotional intelligence, Profile, biology